Pemanfaatan Botol Plastik Bekas Sebagai Wadah Dalam Sistem Hidroponik Untuk Budidaya Sayuran - Wahyu Halya Aprilia Putri; Renita Dwi Lestari; Prasmita Dian Wijayanti (Asosiasi Riset Ilmu Tanaman Dan Hewan Indonesia, 2024)
The residents of RW 05 Jomblang, Candisari District, Semarang City, are increasingly concerned about the impact of plastic waste on the environment. As a solution, used plastic bottles are being utilized as planting media in hydroponic techniques by MBKM students from various universities, such as UPN